Diversity analysis and isolates identification of Bacillus in high-temperature Daqu - HUANG Sixing, WANG Yurong, HE Zihao, TIAN Longxin, ZHOU Jiapin, LIU Juzhen, GUO Zhuang (Zhongguo niangzao, 2024)
In order to explore the diversity of Bacillus in high-temperature Daqu in Xiangyang of Hubei province, the sequencing data with Bacillus relative content>2.0% of high-temperature Daqu samples were downloaded and screened. The diversity of Bacillus in Daqu samples was analyzed by Illumina MiSeq high-throughput sequencing technology combined with traditional pure culture technology. The results showed that there were 12 samples with Bacillus content>2.0% in high-temperature Daqu, including 8 white Daqu samples and 4 yellow Daqu samples. A total of 77 825 representative sequences and 1 197 operational taxonomic units (OTUs) were obtained from all samples. Diversity analysis showed that compared with yellow Daqu, the Chao 1 index and discovered species number of Bacillus in white Daqu samples were significantly higher (P<0.05). OTU analysis showed that OTU5321 and OTU5291 were present in all samples, and the cumulative inclusion sequences in white and yellow Daqu accounted for 49.43% and 41.32% of the total sequences number, respectively. The results of traditional pure culture technology analysis showed that Bacillus amyloliquefaciens was the main cultivable strain of Bacillus in high-temperature Daqu. In conclusion, the richness of Bacillus community structure in white Daqu was higher, and B. amyloliquefaciens was the main culturable strain of Bacillus in high temperature Daqu, which had guiding effect on the application and strain selection of Bacillus in high-temperature Daqu.